Comparación de la adaptación marginal en restauraciones indirectas clase II elaboradas en dos tipos de resinas compuestas nanohíbridas: FORMATM (ULTRADENT®) Y FILTEKTM Z350 XT (3M ESPE®). (2021)
The current needs and demands of patients when facing an oral rehabilitation treatment demand from dentists the constant search for new treatment alternatives with more biocompatible materials and innovative techniques to achieve a more natural appearance and clinical success